YCH Chairman Robert Yap: Building the Logistics Superhighway One Step at a Time - Knowledge@SMU (Institutional Knowledge at Singapore Management University, 2008)
Robert Yap, chairman and CEO of YCH Group, was the featured speaker earlier this year in the Singapore Management University’s Wee Kim Wee Centre CEO Talk series. Over a period of 20 years, Yap led his family-owned business from a small transportation company in Singapore to a leading logistics and supply chain solutions provider in Asia Pacific. In recognition of his visionary leadership and industry expertise, Yap won the Ernst & Young Entrepreneur of the Year Award 2007. He spoke to Knowledge@SMU about YCH’s successful evolution and how the future looks for the company.